In situ electrochemical oxidation-distillation desulfurization of gasoline with electrogenerated dichromate. (2nd June 2020) - Tang, Xiao-dong; Wang, Chun; Li, Jing-jing; Jiao, Shuang; Wang, Zhi-yu; Yang, Liu
Abstract: Cr 3+ contained sulfuric acid aqueous solution and β -PbO2 /Ti anode were prepared for electrochemical oxidation-distillation desulfurization of straight-run gasoline. Strong oxidant (Cr2 O7 2− ) was formed and reacted with organic sulfides. The oxidized sulfides were removed by distillation. Under optimal operating conditions, the desulfurization rate of gasoline reached to 99.16%. β -PbO2 /Ti electrode were characterized by XRD and SEM. Model oil was analyzed by FTIR and GC-MS and the possible desulfurization mechanism was proposed. The recycling experiments of the electrolyte showed its excellent stability, but the concentration of H + in electrolyte should be monitored, since the water will be consumed in electrolysis process, and the over-high H + concentration is not good for the formation of Cr2 O7 2− .